2016
DOI: 10.1142/s0192415x16500348
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of 4β-Hydroxywithanolide E from Physalis peruviana on the Nrf2-Anti-Oxidant System and the Cell Cycle in Breast Cancer Cells

Abstract: 4[Formula: see text]-Hydroxywithanolide E is an active component of the extract of Physalis peruviana that has been reported to exhibit antitumor effects. Although the involvement of reactive oxygen species (ROS) production and the ataxia-telangiectasia mutated protein (ATM)-dependent DNA damage signaling pathway in 4[Formula: see text]-hydroxywithanolide E-induced apoptosis of breast cancer MCF-7 cells was demonstrated in our previous study, the relationship between ROS production and the cellular defense sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 36 publications
0
13
0
2
Order By: Relevance
“…The role of oxidative stress effect in 4βHWE‐induced ROS generation, cell cycle change, and cell death has been reported in breast cancer cells (MCF‐7) by NAC pretreatment. However, this breast cancer study did not consider selective killing and oxidative DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…The role of oxidative stress effect in 4βHWE‐induced ROS generation, cell cycle change, and cell death has been reported in breast cancer cells (MCF‐7) by NAC pretreatment. However, this breast cancer study did not consider selective killing and oxidative DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to enhanced expression of several detoxifying enzymes such as NQO1 and GSTP that play a key role in chemoprevention and therapy of breast cancer by reducing the level of estrogen quinones involved in toxicity and breast carcinogenicity. Recently, Peng et al72 also demonstrated that 4β-hydroxywithanolide E, an active component of the extract of Physalis peruviana , a member of the Solanaceae group, plays an important role in ROS production and subsequent ataxia-telangiectasia mutated protein-mediated apoptosis of breast cancer MCF-7 cells which is correlated with the expression of Nrf2-dependent antioxidative defense enzymes including SOD, CAT, and the glutathione system 72. Accordingly, pretreatment with antioxidants GSH and NAC was capable of reversing the 4β-hydroxywithanolide E-induced ROS accumulation and apoptotic cell death in MCF-7 cells.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, the protein expression of Cdk2 also displays two bands at about 33 kDa. 4β-Hydroxywithanolide E induced a marked increase in the amount of upper band and a significant reduction in the amount of lower band in MCF-7 cells 56 . A G1-phase arrest of the cell cycle was observed when MCF-7 cells were incubated with 4β-hydroxywithanolide E for 24 h in our previous study 56 , whereas fenofibrate induced cell cycle S and G2/M arrest in this study.…”
Section: Discussionmentioning
confidence: 87%
“…4β-Hydroxywithanolide E induced a marked increase in the amount of upper band and a significant reduction in the amount of lower band in MCF-7 cells 56 . A G1-phase arrest of the cell cycle was observed when MCF-7 cells were incubated with 4β-hydroxywithanolide E for 24 h in our previous study 56 , whereas fenofibrate induced cell cycle S and G2/M arrest in this study. Therefore, we indicated that the protein expression of lower band of Cdk2 might play a key role in regulation of the transition from G1 to S phase and S phase progression.…”
Section: Discussionmentioning
confidence: 87%